A rapid and closed-tube method based on the dual-color fluorescence loop-mediated isothermal amplification for visual detection of Atlantic salmon (Salmo salar). (30th March 2023) - Li, Yi; Xue, Hanyue; Fei, Yanjing; Yang, Ying; Huang, Danping; Wang, Libin; Xiong, Xiaohui; Xiong, Xiong
Graphical abstract: Highlights: DNA of Atlantic salmon was amplified with the predicted green fluorescence. All the non-target species emit red fluorescence after amplification. The novel assay with a large contrast color change allows an easy way to discern. As little as 1 fg DNA of Atlantic salmon can be detected with the novel assay. Abstract: Loop-mediated isothermal amplification (LAMP) visual detection based on hydroxyl naphthol blue (HNB) and SYTO 9 is often confounded by the narrow color variation window and the requirement of empirical preset of cutoff intensity value. To improve the suitability for naked-eye inspection, the present work proposed a strategy based on the fluorescence property of SYTO 9 and HNB to enlarge the contrast and a novel dual-color fluorescence LAMP (dfLAMP) assay was developed for visual detection of Atlantic salmon. Specifically, HNB of 26.25 μM, blended with SYTO 9 of 0.75–1.5 μM, was added in the mixture before amplification, producing light green fluorescence for both positive and negative samples. After amplification, green or yellow-green fluorescence was observed for positive samples, while only orange-red fluorescence emitted for negative ones, enabling an easy and rapid distinguish. The optimized dfLAMP assay has proved its specificity and can detect as little as 1 fg Atlantic salmon DNA.